Global, regional, and national epidemiology of childhood neuroblastoma (1990–2021): a statistical analysis of incidence, mortality, and DALYsResearch in context - Jusen Nong; Cheng Su; Changhua Li; Congjun Wang; Wei Li; Yong Li; Peng Chen; Yanqiang Li; Zihao Li; Xinjin She; Zuxin Yuan; Sentian Liu; et al. (EClinicalMedicine)
Summary: Background: Neuroblastoma is the most prevalent extracranial solid tumor in pediatric populations worldwide, representing 8–10% of childhood malignancies and contributing to approximately 15% of pediatric cancer-related fatalities. This study aims to report global trends in the incidence, mortality, and disability-adjusted life years (DALYs) of childhood neuroblastoma from 1990 to 2021. Methods: The study utilized data from the Global Burden of Disease (GBD) database to analyze neuroblastoma incidence, mortality, and DALYs in children aged 0–14 years. Rates for incidence, mortality, and DALYs were calculated per 100,000 population, with 95% uncertainty intervals (UIs). Data from 204 countries and territories were stratified by age, sex, and location. Trends were assessed using Joinpoint regression models to compute the annual percent change (APC) and log-transformed linear regression models to calculate the estimated average annual percentage change (EAPC). Findings: Globally, the incidence of neuroblastoma in children in 2021 was 5560 cases (95% UI, 3734.21–7560.03), with 1977 deaths (95% UI, 1445.04–2528.54), and 174,186.30 DALYs (95% UI, 127,104.64–223,265.92). From 1990 to 2021, the incidence increased by 30.26% (95% UI, −1.24% to 72.51%), mortality by 20.35% (95% UI, −12.44% to 63.30%), and DALYs by 20.08% (95% UI, −12.89% to 63.27%). The incidence rate rose from 0.25 (95% UI, 0.18–0.33) per 100,000 individuals in 1990 to 0.28 (95% UI, 0.19–0.38) per 100,000 individuals in 2021, an overall increase of 12.60% (95% UI, −14.62% to 49.12%). Among the five Sociodemographic Index (SDI) regions, the highest EAPCs were observed in the low-to-mid SDI regions for incidence (1.87%; 95% CI, 1.64%–2.10%), mortality (1.22%; 95% CI, 1.09%–1.34%), and DALYs (1.36%; 95% CI, 1.15%–1.57%). Regionally, Central Asia exhibited the fastest annual increase in incidence (EAPC = 2.76%; 95% CI, 2.18%–3.34%). At the national level, India had the highest number of neuroblastoma cases globally in 2021, with 685 cases (95% UI, 404.16–1007.67). Interpretation: The global trends for incidence, mortality, and DALYs related to pediatric neuroblastoma initially increased and then decreased, although an overall increasing trend was observed. However, the burden of disease remains significant in low-, low-middle-, and middle-SDI regions. A comprehensive understanding of the epidemiology of neuroblastoma in children is crucial for enhancing disease prevention and control efforts. Funding: This research was funded by the Guangxi Natural Science Foundation (Grant No. 2024GXNSFAA010420) and the Youth Science Foundation of Guangxi Medical University (Grant No. GXMUYSF202404).